Effect of phosphine ligand on the optical absorption/emission properties of platinum-containing conjugated polymers. Issue 14 (2nd March 2018) - Miyagi, Yu; Sotani, Taichi; Yajima, Tatsuo; Sano, Natsuhiro; Sanda, Fumio
Abstract : The λ max values of platinum-containing poly(phenyleneethynylene)s with aryl groups bonded to P were higher than those with alkyl groups. Abstract : The Sonogashira–Hagihara coupling polymerization of ad -hydroxyphenylglycine-derived diiodoarylene monomer and platinum-containing diethynylphenylene monomers with various substituents, HCC–C6 H4 –CC–Pt(PR3 )2 –CC–C6 H4 –CCH, 1 : R = C4 H9, 2 : R = C8 H17, 3 : R = cyclohexyl, 4 : R = phenyl, and5 : R = 4-methoxyphenyl, gave the corresponding polymers1′–5′ with number-average molecular weights of 4600–22 000. The polymers were soluble in CHCl3, CH2 Cl2, THF and DMF. CD/UV–vis spectroscopic analysis and dynamic light scattering measurements revealed that1′–5′ formed chirally regulated unimolecular structures in THF/toluene mixtures, while formed chiral aggregates in THF/MeOH mixtures. The conjugation of the polymer main chain was longer for monomers with aryl groups bonded to P compared to monomers with alkyl groups bonded to P. The relationship between the HOMO–LUMO gaps and phosphine ligands was reasonably explained by DFT calculations. The polymers exhibited photoluminescence with quantum yields ranging from 0.003% to 0.9%. The photoluminescence intensity was controlled by changing the phosphine substituents. The thermal stability of the polymers increased and the refractive index decreased as the alkyl chain length of the phosphine ligand was increased.